2004
DOI: 10.1055/s-2004-830121
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy and Efficient Modification of Procedures for Selective Extradural Anterior Clinoidectomy

Abstract: We propose a modified, efficient procedure for selective extradural anterior clinoidectomy, as follows. Drilling is started from the point approximately 9 mm posterior to the lateral margin of the dural insertion into the SOP, and pointed medially in the direction with a right angle to the lateral margin of the ACP. After drilling about 6 mm to reach the lateral border of the OC, unroofing of the OC is carried out to remove the ACP en bloc by fracturing of the optic strut. Using the present procedure, the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
4
11
1
1
Order By: Relevance
“…In the present study the average basal width, length and thickness of the ACP were found to be 7.3 mm, 9.7 mm, and 5.4 mm, respectively. Similar observations were reported by Gupta et al, Hunnargi et al, Huynh-Le et al, Lee et al, and in Nepal, Indian, Japan and Korean skulls, respectively (15,16,20,28). The comparison of the findings revealed that the mean length of ACP is the longest in the Indian population.…”
Section: Dural Fold Vascular and Neural Anatomical Findingssupporting
confidence: 89%
“…In the present study the average basal width, length and thickness of the ACP were found to be 7.3 mm, 9.7 mm, and 5.4 mm, respectively. Similar observations were reported by Gupta et al, Hunnargi et al, Huynh-Le et al, Lee et al, and in Nepal, Indian, Japan and Korean skulls, respectively (15,16,20,28). The comparison of the findings revealed that the mean length of ACP is the longest in the Indian population.…”
Section: Dural Fold Vascular and Neural Anatomical Findingssupporting
confidence: 89%
“…Hunnargi et al (2008), reported in their dry skull study, differences between South Indian, Nepalese and Korean ACP dimensions on both the right and left side. They found that the average length of the right ACP was 10.68±1.90 mm and that of the left Hayashi (2004) and by Gupta et al (2005). Both the right and left ACPs were longer in South Indian skulls than Nepalese and Korean skulls (Gupta et al; Hunnargi et al; Lee et al).…”
Section: Discussionmentioning
confidence: 86%
“…8,[10][11][12] Radical removal of tumors in the suprasellar and parasellar regions, and treatment of aneurysms associated with the internal carotid and upper basilar arteries or intracavernous, requires a detailed knowledge of these regions in terms of their morphology and morphometry: variations are of major surgical significance. 10,13 Knowing the variation in size and shape of the ACP gives an estimate of the location of paraclinoid and cavernous sinus aneurysms. 6 In addition to the presence of the bony caroticoclinoid canal, formed by union of the middle and ACPs, makes the removal of the ACP more difficult and increases the associated risks.…”
mentioning
confidence: 99%